SOEKARNO: HIS MANNERISM AND METHOD OF COMMUNICATION - Wejak, Justin (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
The main purpose of this article is to discuss Soekarno’s mannerism and method of communication. Certain aspects such as Soekarno’s use of language in his speeches are highlighted here in order to provide some basic understanding of Soekarno - both as a person and a political leader of the nation. The article aims at stimulating further discussions concerning this very well known leader. This article also examines Soeharto’s style of speech for a comparison.